Phytochemical studies on herbal plants commonly used for processing and preserving meat and milk - Onyango, C. A.; Gakuya, L. W.; Mathooko, Francis M.; Maina, J. M.; Nyaberi, M.; Mwaura, F (My University, 2014)
Objective: The study aims at identifying and collecting herbal plants commonly used in milk processing and preservation by the Maasai community in Kajiado district and to determine the phytochemical and mineral composition. Methodology and Results: Twenty-three herbal plants were identified; three plants were selected through community prioritization using a structured questionnaire. Analysis for phytochemical composition was done using Sofowara (1993), Trease and Evans (1989) and Harborne (1998) methods composition by AOAC method 923.03 (AOAC, 1995) and pH. Tannins, saponins, flavonoids, alkaloids, steroids, sterols, terpenoids, flavones aglycones and reducing compounds were present in all the herbal plants. The herbal plants were significantly different (P<0.05) in mineral content. The highest mineral content was calcium 90.0 mg/100 g followed by magnesium, zinc and iron. Conclusion and application of the findings: this indicates that these plants are rich in phytochemicals and minerals therefore, they can be exploited to develop nutritive food preservatives because phytochemicals have both antimicrobial and antioxidant properties. These plants can also be processed to obtain a product that will substitute the chemical preservatives in the market now that consumers are showing greater preference for products preserved with natural products. Keywords: phytochemicals, herbs, minerals, antimicrobial